PERIODONTAL OUTCOMES ASSOCIATED WITH CLEAR ALIGNER THERAPY IN ORTHODONTICS: : CURRENT EVIDENCE AND CLINICAL IMPLICATIONS - Rudimar Holler Peres, Rafael; de Castro e Silva, Ana Luisa; de Carvalho Dourado Aragão, Eliane; Campana Magosteiro, Eduardo; Moraes da Silva, Brenda; Menezes Meireles , Juliana; Firmo Chaves Silva, Jonatas; S. Quindos, Danielle; Cesar Soares, Christian; de Oliveira Ribeiro, Samara; et al. (Periódicos Brasil. Pesquisa Científica, 2026)
Clear aligner therapy has become increasingly popular in contemporary orthodontics, especially among adult patients seeking esthetic and comfortable treatment alternatives. Beyond esthetic and biomechanical aspects, its potential influence on periodontal health has attracted growing scientific interest. This review aimed to analyze the current evidence regarding periodontal outcomes associated with clear aligner therapy in orthodontics and to discuss its clinical implications compared with conventional fixed appliances. A narrative literature review was performed based on recent systematic reviews, meta-analyses, randomized controlled trials, and evidence-based reviews addressing periodontal parameters during orthodontic treatment. Current evidence suggests that clear aligners are generally associated with more favorable periodontal conditions, particularly regarding plaque control, gingival inflammation, bleeding on probing, and probing depth, when compared with fixed appliances. However, these advantages appear to be modest and are strongly influenced by confounding variables such as oral hygiene compliance, patient motivation, professional periodontal maintenance, and treatment complexity. In periodontally compromised patients, orthodontic treatment may be performed safely after periodontal stabilization, provided that interdisciplinary planning and close periodontal monitoring are maintained. Although available evidence supports the periodontal benefits of clear aligners in selected clinical situations, further high-quality longitudinal and randomized studies are needed to better define their long-term periodontal effects and clinical relevance.